Substrate-Integrated Waveguide PCB Leaky-Wave Antenna Design Providing Multiple Steerable Beams in the V-Band - Matthias Steeg (Electronics, 2017)
A periodic leaky-wave antenna (LWA) design based on low loss substrate-integrated waveguide (SIW) technology with inset half-wave microstrip antennas is presented. The developed LWA operates in the V-band between 50 and 70 GHz and has been fabricated using standard printed circuit board (PCB) technology. The presented LWA is highly functional and very compact supporting 1D beam steering and multibeam operation with only a single radio frequency (RF) feeding port. Within the operational 50–70 GHz bandwidth, the LWA scans through broadside, providing over 40° H-plane beam steering. When operated within the 57–66 GHz band, the maximum steering angle is 18.2°. The maximum gain of the fabricated LWAs is 15.4 dBi with only a small gain variation of +/−1.5 dB across the operational bandwidth. The beam steering and multibeam capability of the fabricated LWA is further utilized to support mobile users in a 60 GHz hot-spot. For a single user, a maximum wireless on-off keying (OOK) data rate of 2.5 Gbit/s is demonstrated. Multibeam operation is achieved using the LWA in combination with multiple dense wavelength division multiplexing (WDM) channels and remote optical heterodyning. Experimentally, multibeam operation supporting three users within a 57–66 GHz hot-spot with a total wireless cell capacity of 3 Gbit/s is achieved.